Diverse effects of invasive ecosystem engineers on marine biodiversity and ecosystem functions: A global review and meta‐analysis. (4th January 2018) - Guy‐Haim, Tamar; Lyons, Devin A.; Kotta, Jonne; Ojaveer, Henn; Queirós, Ana M.; Chatzinikolaou, Eva; Arvanitidis, Christos; Como, Serena; Magni, Paolo; Blight, Andrew J.; Orav‐Kotta, Helen; Somerfield, Paul J.; et al.
Abstract: Invasive ecosystem engineers (IEE) are potentially one of the most influential types of biological invaders. They are expected to have extensive ecological impacts by altering the physical–chemical structure of ecosystems, thereby changing the rules of existence for a broad range of resident biota. To test the generality of this expectation, we used a global systematic review and meta‐analysis to examine IEE effects on the abundance of individual species and communities, biodiversity (using several indices) and ecosystem functions, focusing on marine and estuarine environments. We found that IEE had a significant effect (positive and negative) in most studies testing impacts on individual species, but the overall (cumulative) effect size was small and negative. Many individual studies showed strong IEE effects on community abundance and diversity, but the direction of effects was variable, leading to statistically non‐significant overall effects in most categories. In contrast, there was a strong overall effect on most ecosystem functions we examined. IEE negatively affected metabolic functions and primary production, but positively affected nutrient flux, sedimentation and decomposition. We use the results to develop a conceptual model by highlighting pathways whereby IEE impact communities and ecosystem functions, and identify several sources of research bias in the IEE‐related invasion literature. Only a few of the studies simultaneously quantified IEE effects on community/diversity and ecosystem functions. Therefore, understanding how IEE may alter biodiversity–ecosystem function relationships should be a primary focus of future studies of invasion biology. Moreover, the clear effects of IEE on ecosystem functions detected in our study suggest that scientists and environmental managers ought to examine how the effects of IEE might be manifested in the services that marine ecosystems provide to humans. Abstract : The summary effects of invasive ecosystem engineers (IEE) on 10 response categories as Hedges' g. The overall effects of IEE on community abundance and diversity were non‐significant, however, there was a strong overall effect on most ecosystem functions.